Investigation of gait characteristics in the elderly population in Singapore for diagnosis of sarcopenia and related observations in knee MRI. - Singh Gautam. (2012)
Sarcopenia is defined as the loss of muscle mass, strength and function with age. It is characterized by a lower skeletal muscle quantity, higher fat accumulation in the muscle, lower muscle strength, and lower physical performance. Therefore, the consequence of sarcopenia results in the increased risk of falls which is indicative of adverse health outcomes including disability, injuries and institutionalization in hospitals. A frailty paradigm is thus needed in primary care to identify the risk of falling in the fall prone elderly individuals. However, the appropriate metrics at that level are still lacking. Through literature review, it was found that the muscle infiltrate such as fat plays a considerable role in weakening muscle strength by lowering muscle mass. Magnetic resonance imaging (MRI) is the most specific standard for assessing muscle mass or cross sectional muscle area. MRI has been proven to be a powerful tool to accurately derive muscle and bone volume from soft tissues which can be used in highlighting the onset of sarcopenia.